1998
DOI: 10.1007/bf02481533
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the moisture storage characteristics of porous capillary active materials

Abstract: A B S T R A C T R i~ S U M i~With new improved calculation models a good agreement between computed and measured results of moisture transfer is obtainable on condition that correct material properties are used. Especially when capillary active materials are in hygric connection, their moisture storage characteristics have a predominant influence on the moisture behaviour of the building component. In this contribution, a pressure plate method to determine the moisture storage characteristics in the capillary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 9 publications
(9 reference statements)
0
18
0
6
Order By: Relevance
“…In this section, based on the numerical model of the uncracked concrete and amendatory chloride migration equation (6), the e ect of relative humidity in concrete on chloride migration is discussed. In general, moisture exists in pores of concrete in gaseous state and liquid state when the relative humidity in concrete is less than 45% and more than 45%, respectively [29]. erefore, chloride migration concentration distribution pro les under 50%, 70%, and 100% relative humidity in concrete are simulated in this study, and the results are shown in Figure 8.…”
Section: E Ect Of Relative Humidity On Chloridementioning
confidence: 97%
“…In this section, based on the numerical model of the uncracked concrete and amendatory chloride migration equation (6), the e ect of relative humidity in concrete on chloride migration is discussed. In general, moisture exists in pores of concrete in gaseous state and liquid state when the relative humidity in concrete is less than 45% and more than 45%, respectively [29]. erefore, chloride migration concentration distribution pro les under 50%, 70%, and 100% relative humidity in concrete are simulated in this study, and the results are shown in Figure 8.…”
Section: E Ect Of Relative Humidity On Chloridementioning
confidence: 97%
“…above 93-95% RH, the sorption isotherms become extremely steep and slight variations in relative humidity result in large changes in moisture content. Thus, the higher part of the moisture storage curve must be completed by other means, namely pressure plate experiments or results derived from mercury porosimetry [41].…”
Section: Static Gravimetric Testsmentioning
confidence: 99%
“…For comparative studies and characterization, equivalent pore sizes obtained from estimated suctions are often compared with MIP results while considering the Washburn's equation (Washburn, 1921) as a conversion tool (Krus and Kießl, 1998;Aung et al, 2001Aung et al, , 2008. Taking this into consideration, the estimated suctions are converted to equivalent pore size.…”
Section: Pore Size Distributionmentioning
confidence: 99%